Petrogenesis of microgranitoid enclaves and their host granites: The example of Late Cretaceous Guyong pluton in Tengchong Block, SW China. Issue 1 (11th October 2021) - Sun, Zhuanrong; Dong, Guochen; Ketchaya, Yanick Blaise; Pan, Yanning; Wang, Weiqing; Xu, Ling; Guo, Jianheng; Wang, Zhongbao; Fu, Bin
Abstract : Granitoids and their hosted microgranitoid enclaves (MEs) can provide crucial information in understanding the evolution of granitoids and continental crustal growth. The Guyong pluton in central Tengchong Block is mainly composed of monzogranites and abundant coeval MEs (76 Ma). This study reports their petrological, geochemical, and Sr–Nd, zircon U–Pb, and Lu–Hf–O isotopic features to shed light on their petrogenesis and the evolution of the Neo‐Tethys. The Guyong MEs have low SiO2 (56.88–69.61 wt%) and high MgO (1.04–3.91 wt%) contents. They have typical igneous textures and are characterized by similar mineral assemblages, chondrite‐normalized rare earth element diagrams, and Sr–Nd and zircon Hf–O isotopic compositions (εHf (t) of −9.0 to −2.3, δ 18 O of 6.57–8.07) with their host monzogranites, indicating that they are cognate. The acicular apatite and fine‐grained texture and geochemical characteristics suggest that the MEs were generated in a rapid cooling and crystallization process at the margin of magma conduit. The Guyong monzogranites have high SiO2 contents (70.79–74.24 wt%) and low MgO contents (0.24–0.78 wt%). They are calc‐alkalic and weakly peraluminous and show characteristics of I‐type granites. The geochemical and isotopic compositions of the Guyong monzogranites and MEs suggest that they were produced by partial melting of the metasedimentary and meta‐igneous rocks from the Proterozoic Gaoligong metamorphic complex. The Late Cretaceous magmatism in the central Tengchong Block is correlated with the northward subduction of the Neo‐Tethys. Abstract : The microgranitoid enclaves (MEs) are microgranular and contain acicular apatite and mainly distribute in the margin of the host monzogranite, suggesting a rapid cooling process occurred at the margin of magma conduit. They show characteristics of liquid‐crystal mushes and similar to cumulates. Therefore, we propose a model of rapid cooling and crystallization at the margin of magma conduit for the genesis of the Guyong MEs.